Rapid shoreline progradation followed by vertical foredune building at Pedro Beach, southeastern Australia. Issue 2 (19th October 2018) - Oliver, Thomas S.N.; Tamura, Toru; Short, Andrew D.; Woodroffe, Colin D.
Abstract: At Pedro Beach on the southeastern coast of Australia a series of foredune ridges provides an opportunity to explore the morphodynamic paradigm as it applies to coastal barrier systems using optically stimulated luminescence (OSL) dating, ground penetrating radar (GPR) and airborne LiDAR topography. A series of sandy dune‐capped ridges, increasing in height seawards, formed from c . 7000 years ago to c . 3900 years ago. During this time the shoreline straightened as the embayment filled and accommodation space for Holocene sediments diminished. Calculation of Holocene sediment accumulation above mean sea level utilising airborne LiDAR topography shows a decline in average sediment supply over this time period coupled with a decrease in shoreline progradation rate from 1.2 m/yr to 0.38 m/yr. The average ridge 'exposure lifetime' during this period increases resulting in higher ridges as dune‐forming processes have longer to operate. Increasing exposure to wave and wind energy also appears to have resulted in higher ridges as the sheltering effect of marginal headlands was diminished. An inherited disequilibrium shoreface profile will drive onshore accumulation of sandy sediments forming a prograded barrier; however, if there is no longer 'accommodation space' for sediment, this will be an overriding factor causing the cessation of progradation, as occurred c . 3900 years ago at Pedro Beach. Excess sediment in the nearshore zone after 3900 years ago may have been moved northward to nourish downdrift beaches in the compartment. A high outer foredune has formed through vertical accretion after 500 years ago, evidenced by GPR subsurface structures and OSL ages, with a distinct period of vertical and lee slope accretion and dated to the period 1890–1930 AD. The increased dune sediment transport resulting in foredune building is attributed to recent human disturbance. © 2018 John Wiley & Sons, Ltd. Abstract : Rapid shoreline progradation followed by shoreline stability and foredune building at Pedro Beach, southeastern Australia demonstrates the importance of geological inheritance as a morphodynamic factor controlling sandy shoreline evolution. In this case, embayment filling with beach, nearshore and dune sediments, has effectively halted any further shoreline progradation potential as the inherited accommodation space for Holocene sediments is full.